2012
DOI: 10.6061/clinics/2012(09)05
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of celiac disease among blood donors in SÃO PAULO – the most populated city in Brazil

Abstract: OBJECTIVE:Celiac disease is a permanent enteropathy caused by the ingestion of gluten, which leads to an immune-mediated inflammation of the small intestine mucosa. The prevalence of celiac disease varies among different nations and ethnic backgrounds, and its diversity is determined by genetic and environmental factors. São Paulo city is one of the largest cities in the world, with a vast population and an important history of internal migratory flow from other Brazilian regions, as well as immigration from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
0
28
0
6
Order By: Relevance
“…This contrasts with the vast experience that is published on the subject, especially in countries such as Brazil (11) or Argentina (10) . Even though dyspepsia prevalence is much higher than the expected prevalence of CD in the general population, CD prevalence in Latin American countries has been shown to be comparable to the prevalence from North American or European countries (1) . As a consequence, our experience in this matter may be paralleled to the experiences in other regions of the World.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the vast experience that is published on the subject, especially in countries such as Brazil (11) or Argentina (10) . Even though dyspepsia prevalence is much higher than the expected prevalence of CD in the general population, CD prevalence in Latin American countries has been shown to be comparable to the prevalence from North American or European countries (1) . As a consequence, our experience in this matter may be paralleled to the experiences in other regions of the World.…”
Section: Discussionmentioning
confidence: 99%
“…This study contained patients with clinical complaints, which is unusual for a seroprevalence study but has been described by other authors 32,37 . All patients reported abdominal pain (100%, p = 0.008), whereas only 40% complained of diarrhea, which is the classic symptom of the disease 1 .…”
Section: Characteristics Of Individuals With Positive Serology For Cementioning
confidence: 99%
“…A similar study conducted in São Paulo evaluated 4,000 serum samples from blood donors, and 24 showed positive serology: 11 were TTG-and EMA-positive, 10 were only TTG-positive and three were only EMA positive. Among the 21 patients who underwent duodenal biopsy, six (29%) patients had some histological abnormality 37 .…”
Section: Characteristics Of Individuals With Positive Serology For Cementioning
confidence: 99%
“…(5)(6)(7). En São Paulo la prevalencia de la enfermedad celíaca es del 0,6%, la cual es similar a las tasas reportadas en Portugal e Italia (5,7,8). Un diagnóstico positivo de la enfermedad celíaca se lleva a cabo por la presencia de transglutaminasa antitejido (tTG) y anticuerpos endomisiales (EMA) en los exámenes serológicos.…”
Section: Introductionunclassified